Efecto de la humedad en dos variedades de maíz sobre los costos de molienda - Zambrano Zambrano, Charly Sebastian (2020)
The objective of the research was to evaluate the effect of humidity in two varieties of corn on milling costs. A DBCA was applied to determine if the variety or humidity influenced the treatments studied and a DCA with the humidity percentages of 17,15 and 13 in both varieties of corn (hard yellow THUNDER NB-7443 and hard white PICHILINGUE 513), with a total of six treatments with three replicates. The experimental unit was 4,545kg. Also evaluating the fungal quality of the ground corn, resulting in the varieties not influencing the milling costs, but it should be noted that the humidity does influence, which results in the treatment of T3 (hard yellow corn THUNDER NB-7443 with a content of 13% moisture), at a cost of $4.03 US dollars, value that would represent grinding a ton of it. It is worth mentioning that the fungal quality (molds and aflatoxins) was determined for these treatments, showing that both parameters evaluated were within the provisions of the NTE INEN 187 (2013) regarding molds and NTE INEN 187 (1995) in aflatoxins. It was concluded that the most suitable percentage to carry out corn grinding processes is 13% (T3).